A clinical and histopathological study of nevus sebaceous - Puri, Neerja (Journal of Pakistan Association of Dermatologists, 2016)
Objective To study the clinical and histopathological features of nevus sebaceous (NS). Methods We selected 20 cases of nevus sebaceous for clinical and histopathological evaluation. Results Regarding the clinical appearance of lesions verrucous plaques were seen in 60% patients, papules in 25% and patches in 15%. All of the lesions showed abortive/immature hair follicles characterized by cords of undifferentiated, basaloid cells resembling the embryonic stages of hair follicle. Conclusion NS is a hamartoma consisting of various elements indigenous to the organ and not merely the sebaceous units.